2005
DOI: 10.1007/s10865-005-9026-3
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Clinical Trial of Blood Glucose Awareness Training (BGAT III) in Switzerland and Germany

Abstract: Although both diabetes and the efficacy of medical management are international issues, psycho-educational interventions might be culturally bound. Blood Glucose Awareness Training (BGAT) is a psycho-educational program for patients with type 1 diabetes mellitus. It is focused on improving recognition and management of extreme blood glucose levels, and is the best documented American psycho-educational program for this purpose. A randomized controlled clinical trial of BGAT's long-term benefits in a non-Americ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
0
8

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(88 citation statements)
references
References 24 publications
1
79
0
8
Order By: Relevance
“…Glycemic control improved in the U.S.-based BGAT studies (47,48) in both control and intervention groups, but showed no change in the European-BGAT (45). PRIMAS showed improvement in HbA 1c only in the intervention arm (42).…”
Section: Educationmentioning
confidence: 90%
See 1 more Smart Citation
“…Glycemic control improved in the U.S.-based BGAT studies (47,48) in both control and intervention groups, but showed no change in the European-BGAT (45). PRIMAS showed improvement in HbA 1c only in the intervention arm (42).…”
Section: Educationmentioning
confidence: 90%
“…These studies did not report baseline SH rates (47,48) and people with SH in the preceding 2 years of the study were excluded from the Kinsley et al (47) study. In the European-BGAT study (45), people with recurrent SH were encouraged to participate: SH fell by 88% in the BGAT group compared with the physicianguided self-help control group, which showed no reduction in SH rates. A head-to-head comparison between PRIMAS (42), a new German education program with additional aspects of goalsetting, motivation, and greater hypoglycemia focus, against the well-established DTTP (39) showed equivalent reductions in SH in both intervention and control groups.…”
Section: Educationmentioning
confidence: 99%
“…Blood glucose awareness training is an alternative standard self-management program approach that proved to decrease the rate of severe hypoglycemia in type 1 diabetes (15,16). In a 12-month uncontrolled trial, blood glucose awareness training reduced the rate of severe hypoglycemia from 19.2 to 13.2 events ⅐ patient Ϫ1 ⅐ year Ϫ1 (17).…”
Section: Sä Mann and Associatesmentioning
confidence: 99%
“…There may be many reasons for these problems with compliance. A known important predictor of good compliance is the patient's own confidence in their ability to control their disease [17][18][19], which in psychology has been described by the term 'locus of control'. Locus of control defines the attitudes of people with regard to the control they have over their life.…”
Section: Introductionmentioning
confidence: 99%